2014 IEEE International Ultrasonics Symposium 2014
DOI: 10.1109/ultsym.2014.0057
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound backscatter parameters in the human cervix

Abstract: Quantitative ultrasound has been investigated as a tool for monitoring cervical changes that might result in preterm birth. Backscatter parameters, specifically attenuation and the backscattered power loss (BSPL), appear to be two important parameters. Sources of potential variability such as the angle of the beam interrogating the cervix, the region within the cervix, the number of previous births, and the state of ripening, have not been systematically examined, but could contribute to bias and variance in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Our recent studies in nonpregnant ripened versus unripened hysterectomy specimens demonstrated that controlling for expected sources of anatomical variation in collagen structure significantly reduces variance in attenuation estimates (Guerrero et al, 2014). Studies in structurally aligned tissues have shown that attenuation is dependent on the angle between the acoustic beam and structural orientation (Insana et al, 1992; Mottley and Miller, 1990; Nassiri et al, 1979; Topp and O'Brien, 2000) and attenuation versus steering angle provides evidence for aligned structures in the cervical ECM (presumably collagen).…”
Section: Cervical Tissue Mechanical Propertiesmentioning
confidence: 99%
“…Our recent studies in nonpregnant ripened versus unripened hysterectomy specimens demonstrated that controlling for expected sources of anatomical variation in collagen structure significantly reduces variance in attenuation estimates (Guerrero et al, 2014). Studies in structurally aligned tissues have shown that attenuation is dependent on the angle between the acoustic beam and structural orientation (Insana et al, 1992; Mottley and Miller, 1990; Nassiri et al, 1979; Topp and O'Brien, 2000) and attenuation versus steering angle provides evidence for aligned structures in the cervical ECM (presumably collagen).…”
Section: Cervical Tissue Mechanical Propertiesmentioning
confidence: 99%
“…In fact, in the cervix, attenuation has been shown to be affected by angle of interrogation and location (distal versus proximal cervix). 39 Therefore, measuring attenuation without accounting for sources of potential variability such as beam angle could contribute to estimate bias and variance.…”
Section: Quantifying Cervical Remodelingmentioning
confidence: 99%
“…Our initial studies involved using (nonpregnant) hysterectomy specimens to verify shear wave speed estimates (SWS) and backscatter parameters (e.g. mean backscattered power difference, mBSPD) with actual tissue microstructure examined via nonlinear optical microscopy imaging in both Rhesus (Guerrero, 2018) and women (Guerrero et al, 2018b). Subsequently, we demonstrated in vivo with SWS that the cervix progressively softens as pregnancy advances in the Rhesus (Rosado-Mendez et al, 2017, 2018 and that the human cervix is significantly softer in late, as opposed to early, pregnancy (Carlson et al, 2015(Carlson et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The transducer was placed in the rectal cavity and the cervix identified via palpation and identification (from the B-mode image) of anatomical landmarks (uterus, bladder, internal os, external os, and cervical canal). Data were acquired from the "transition zone", an area in the macaque cervix between the internal os and the tortuous distal canal, (Rosado-Mendez et al, 2017) where the cervix appears nearly identical to that of the human (primarily, the canal is relatively straight) (Rosado-Mendez et al, 2017, 2018. Raw radiofrequency (RF) echo signal data were captured using the Axius Direct Ultrasound Research Interface (Brunke et al, 2007) with 40 MHz sampling of the RF echo signals.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation